PENGUASAAN KOSAKATA DAN KECERDASAN INTERPERSONAL SISWA DENGAN KEMAMPUAN MENULIS KARANGAN NARASI SISWA - Tatu Hilaliyah (Jurnal Membaca Bahasa dan Sastra Indonesia, 2017)
This study aims to determine (1) whether there is a relationship vocabulary with narrative essay writing skills; 2) the relationship of interpersonal intelligence students with narrative essay writing skills; (3) the relationship vocabulary and interpersonal intelligences of students together with the ability to write a narrative essay. The method used is the correlation method. Samples were students of class VII IT Raudhatul Jannah totaling 50 students memorandum. Data was collected using tests and questionnaires. Variable narrative essay writing skills used in the form of test instruments fabricate, interpersonal intelligence variable instruments that are used in the form of a closed questionnaire, variable vocabulary of data obtained by multiple-choice test. The data were analyzed using inferential analysis F test and t test with SPSS 22 for windows. The results show that (1) there is a significant relationship between vocabulary with the ability to write narrative essays rhitung (0,687)> rtable (0.443), the correlation coefficient was tested by t test, the results tcount (4,010)> Table (1,734); (2) there is a significant relationship between students' interpersonal intelligence with the ability to write a narrative essay rhitung price (0.778)> rtable (0.443), the correlation coefficient was tested by t test, the results tcount (5.256)> Table (1,734); (3) there is a significant correlation between vocabulary and interpersonal intelligences of students together with the ability to write a narrative essay Ry (1,2) amounted to 0,829, the coefficient korelasi signifikansi with F-test obtained F count = 18.701, the real level α = 0, 05, with 19 df obtained Ftable = 3.52 then Fhitung> Ftable. Thus, it can be concluded that the mastery of vocabulary and interpersonal student has a significant relationship with students' ability to write narrative essays.